Generation of secondary microbial methane of high-rank coals: insights from the microbial community and carbon isotope - Nai, Hui; Xu, Sheng; Chen, Biying; Zhong, Jun; Fang, Lujia; Qin, Sirou; Sano, Yuji (Frontiers in Microbiology, 2024)
Secondary microbial methane could provide a valuable energy source if it were better understood. Although coal seam is an ideal environment for investigating secondary microbial methane, there are few studies to trace the secondary microbial methane of high-rank coals. Here, we collected co-produced water samples from coalbeds in the Qinshui Basin (China) and analyzed the microbial community structure by 16S ribosomal RNA (16S rRNA) amplicon sequencing analysis. 16S rRNA sequencing demonstrated abundant methanogens in coalbeds including 6 orders (Methanobacteriales, Methanococcales, Methanofastidiosales, Methanomassiliicoccale, Methanomicrobiales, and Methanosarciniales) and 22 genera of methanogens. Superheavy DIC (δ13CDIC ranging from −4.2‰ to 34.8‰) and abundance of methanogenic microbes in co-produced water revealed the generation of secondary biogenic methane in high-rank coal seams in the Qingshui Basin. Hydrogenotrophic methanogenesis is the main pathway for secondary biogenic methane production. In deeply buried coal seams, biogenic methane is dominated by CO2 and H2 reduction methanogenesis, and in shallow buried coal seams, it may be produced synergistically by hydrocarbon degradation and hydrogenotrophic methanogenic microbes. The study discussed here is important for a better understanding of the generation of secondary microbial methane in high-rank coal.